The Influence of Promotion Through Instagram On Purchasing Decisions For Processed Fish Products at Dakon Frozen Food Sleman, Yogyakarta - Ridwan, Muhammad; Ilyas; Halisa, Nur; Zam, Wahyuni (Jurnal IPTEKS Pemanfaatan Sumberdaya Perikanan, 2024)
Promotion is important in marketing activities, especially in increasing traffic, known as online promotion. Along with the development of increasingly sophisticated technology, the internet is no stranger to marketing a product. An effort to sell a product or service using Internet media can also be called e-marketing. This study aimed to know the effect of promotion through instagram on purchasing decisions for processed fish products at Dakon Frozen Food Sleman, Yogyakarta. The quantitative data of this study are questionnaires distributed to consumers of Dakon Frozen Food Yogyakarta. The sample used in this study were instagram users, with a sample size of 40. The data sources used are primary data and secondary data. The data collection technique used was distributing questionnaires. The data analysis techniques researchers use are simple linear regression, validity test, reliability test, normality test, linearity test, simple linear regression test, correlation coefficient test, determination coefficient test, and hypothesis testing. The results showed that the simple regression analysis equation obtained was Y = 11.242 + 0.756X + e. Instagram promotion (X) significantly influences the purchasing decision variable (Y), with a coefficient of 11.242. In testing the hypothesis using the t-test, the t-count value of the Instagram promotion variable is 11.242> from the table, which is 2.026 and a significant value of 0.000 <0.05. This means that H1 is accepted, namely: There is an influence of Instagram promotion on purchasing decisions for processed fish products at Dakon Frozen Food Sleman, Yogyakarta